Bali dalam Tarikan Pembangunan Berkelanjutan - Suarna, I Wayan (Badan Riset dan Inovasi Daerah Provinsi Bali, 2018)
With the enactment of a global agenda known as the Sustainable Development Goals (SDGs), all local governments must mainstream the environment in various government programs and policies. The mainstreaming is carried out because of the increase in anthropogenic activities which are predicted to have an impact on the existence of development and the environment. The Province of Bali has a variety of traditional wisdom that has significantly contributed greatly to environmental services and the provision of environmental services. However, increasing population growth has the potential to reduce environmental quality because of the excessive exploitation of natural resources without taking into account the sustainability of Bali's natural resource functions that have limitations. Related to this, the sensitivity and alignments of the environment that were patterned in the SDGs from various stakeholders need to be improved in an effort to build togetherness to conduct environmental management holistically.